HDI XMAS July 15, 2019. Geraldine Legge photos. - Barrett, Terra
A black and white photo of carollers (standing) Stewart Reid, Leo Reid, Hedley Fost, Arthur Crocker, Joe Crocker, Jim Reid, Robert Howell, Harrison Bishop, Eleck Crocker, James Bishop, (crouching) Calvin Legge, Albert Reid, Raymond Legge, Geraldine as a girl at Annie Legge's house in Heart's Delight.